Optimization of a PV/microturbine hybrid system for tropical climates - Ismail M.S.; Moghavvemi M.; Mahlia T.M.I. (2023)
Hybrid system based on photovoltaic is considered an effective option to electrify remote and isolated areas far from grid. This is true for areas that receive high averages of solar radiation annually. Using microturbine as a standby source will make utilization of hybrid systems more attractive. A sizing optimization of the hybrid system components, an economic feasibility study and a complete design of the hybrid system consisting of photovoltaic (PV) panels, a microturbine as a backup power source and a battery system supplying a small community in a tropical climate area were presented in this paper. A scenario depending on PV standalone and another scenario depending on microturbine alone were also studied and analyzed in this paper. This is to select the most appropriate considering cost and pollutant emissions for these areas. A simulation program depending on an iterative approach was used to optimize the sizes of PV system and battery bank. Specifications of the hybrid system components are then determined according to the optimized values. Solar radiation data is firstly analyzed and the tilted angle of the PV panels is also optimized. It is found that electrifying rural small community using this hybrid system is very beneficial and competitive with other types of conventional sources as it decreases both operating costs and pollutant emissions. 2013 IEEE.